2021
DOI: 10.3389/fmicb.2021.761836
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome-Mediated Alteration of Immunity, Inflammation, and Metabolism Involved in the Regulation of Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the leading causes of end-stage liver disease, leading to a rapidly growing global public health burden. The term “gut microbiome (GM)” refers to the approximately 100 trillion microbial cells that inhabit the host’s gastrointestinal tract. There is increasing evidence that GM is involved in the pathogenesis of NAFLD and may be a potential target for intervention. To explore GM-based strategies for precise diagnosis and treatment of NAFLD, great efforts have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 145 publications
(126 reference statements)
0
27
0
Order By: Relevance
“…Moreover, we found that PDX treatment significantly modulated the gut microbiota structure in obese mice. Previous studies have indicated that gut microbiota dysbiosis is one of the reasons for obesity and related disorders, and fecal microbial transplantation (FMT) is considered a potential source of novel therapeutics (Napolitano and Covasa, 2020;He et al, 2021;Voland et al, 2021). FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that PDX treatment significantly modulated the gut microbiota structure in obese mice. Previous studies have indicated that gut microbiota dysbiosis is one of the reasons for obesity and related disorders, and fecal microbial transplantation (FMT) is considered a potential source of novel therapeutics (Napolitano and Covasa, 2020;He et al, 2021;Voland et al, 2021). FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the abnormal hepatic lipid metabolism is involved in sustained inflammation response and liver injury, further leading to the progression of NAFLD (Dong et al, 2021;Orabi et al, 2021). Apart from the aberrant hepatic lipid metabolism, gut microbiome-mediated alteration of immunity, inflammation, and metabolism are also involved in the regulation of NAFLD (He et al, 2021). Currently, no specific drug has been approved to treat NAFLD, though several candidate drugs with different mechanisms of action have been tested in clinical trials (Brown et al, 2021), which target different pathophysiological pathways towards NAFLD, such as metabolic targets, inflammatory pathways, liver-gut axis, and antifibrotic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the abnormal hepatic lipid metabolism is involved in sustained inflammation response and liver injury, further leading to the progression of NAFLD ( Dong et al, 2021 ; Orabi et al, 2021 ). Apart from the aberrant hepatic lipid metabolism, gut microbiome-mediated alteration of immunity, inflammation, and metabolism are also involved in the regulation of NAFLD ( He et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…NAFPD and nonalcoholic fatty liver disease (NAFLD) have been linked to metabolic syndrome, and they likely share a similar pathogenesis [94,95]. The gut microbiota may trigger NAFLD through several mechanisms: Increase in intestinal permeability, modulation of the innate immune system, alteration of bile acid turnover, increase in endogenous ethanol production, and triggering of direct and indirect inflammatory stimuli [96]. Similar mechanisms could be claimed for the pathogenesis of NAFPD.…”
Section: Non-alcoholic Fatty Pancreatic Disease (Nafpd)mentioning
confidence: 99%